The role of microRNAs in prethrombotic status associated with coronary artery disease - Gao, Jie; Ma, Xiaojuan; Zhang, Ying; Guo, Ming; Shi, Dazhuo (Thrombosis and Haemostasis, 2017)
The acute cardiovascular events following thrombus formation is a primary cause of morbidity and mortality of patients with coronary artery disease (CAD). Numerous studies have shown that a prethrombotic status, which can be defined as an imbalance between the procoagulant and anticoagulant conditions, would exist for a period of time before thrombogenesis. Therefore, early diagnosis and intervention of prethrombotic status are important for reducing acute cardiovascular events. However, none of prethrombotic indicators have been identified as golden standard for diagnosis of prethrombotic status to date. MicroRNAs (miRNAs), a class of short non-coding RNAs, have been shown to be involved in pathophysiologic processes related to prethrombotic status, such as endothelial dysfunction, platelet activation, impaired fibrinolysis and elevated procoagulant factors, etc. Owing to their multiple and fine-tuning impacts on gene expression, miRNAs raise a novel understanding in the underlying mechanism of prethrombotic status. This review aims to discuss the role of miRNAs in prethrombotic status, especially the differently expressed miRNAs in CAD, which may be meaningful for developing promising diagnostic biomarkers and therapeutic strategies for CAD patients in future.
Keywords: MicroRNAs; prethrombotic status; coronary artery disease; biomarkers